The empire is dead, long live the empire long-run persistence of trust and corruption in the bureaucracy - Becker, Sascha O. (2016)
We hypothesise that the Habsburg Empire with its well-respected administration increased citizens' trust in local public services. In several Eastern European countries, communities on both sides of the long-gone Habsburg border have shared common formal institutions for a century now. We use a border specification and a two-dimensional geographic regression discontinuity design to identify from individuals living within a restricted band around the former border. We find that historical Habsburg affiliation increases current trust and reduces corruption in courts and police. Falsification tests of spuriously moved borders, geographic and pre-existing differences and interpersonal trust corroborate a genuine Habsburg effect. - Reproduced.
Keywords: Corruption; Bureaucracy